Role of the culture for formation of the attitude - Abdullayeva Shafahat, (Technium Social Sciences Journal, 2020)
There are deep relations between the human mind and the environment. The surroundings of human sarefilled with influences from past generations. Therefore, humans are shaped by the character of the world. The analysis of psychological literature concludes that children become the object of culture from birth. In the process of socialization, a child learns other scenarios from their culture. The state of mind interiorized all of these cultural scenarios. This process impacts aperson’s perception of the external world. Such influences impact the formation of conscious perception and the emotional system. Mentalities, emotions of the human mind were studied in this article as an internal factor which affects human attitude. It is demonstrated that it is impossible to think about the formation of a child’s perception of the world without, considering all of these factors. The internal factors are formed by knowledge of the world, modes of behaviour and scenarios which were learned during childhood. The sources of this knowledge, modes of behaviours and scenarios are culture driven. The basis of psychology is connected to a specific culture. Culture affects the perception of the mind’s formulation; the “cultural frame” of perception. The objects of the external world have mental meaning, which pass through the cultural frame of perception. The ways of cultural formation and the perception of it affect the formation of human attitude. The culture learned by an individual are related to the ‘thoughtless’ or ‘thoughtful’ attitude which are manifested by certain actions. The investigation showed that culture is the framework for attitude and a person reflects specific cultural attitudes.